Educational and Human Rights in Poland - Kwiek, Marek (Antwerpen: Wolf Legal Publishers, 2004)
Poland signed the European Convention on Human Rights on November 26, 1991 and ratified it on January 19, 1993. Consequently, Polish education has been under direct influence of the Convention for a decade now. Its influence has been strong on the level of policy-making and law-making in various aspects of education (after the fall of Communism in Poland in 1989, education of all levels gained autonomy and independence from centralized state control prevalent in 1945-1989; new laws were passed in both primary and secondary education (1991) and higher education (1990), with amendments in the folowing years). Major Polish debates relating the Convention to educational issues were devoted to religious instruction in public primary and secondary schools, teaching sexual education in early primary school and, to a smaller degree, the rights of the parents in education, often in connection with the first two issues. Neither health education nor the use of corporal punishment in schools were much debated. Therefore it is mostly in relation to teaching religion and sex education in public schools that the Convention was referred to in Poland in recent years in connection with education.
Keywords: Poland; human rights; education; European Convention on Human Rights; ECHR; the right to education; edcuation as human rights; communism; religious education; constitutional rights; education for all; primary and secondary education; Polish reforms; postcommunist transformations